ENT 530 Social Media Portfolio: Monsterwiches / Nor Syazana Abdullah - Abdullah, Nor Syazana (2021)
Monsterwiches are premium sandwiches that are given a special touch in terms of the ingredients used to produce the core differently from the others. Other than that, it available in 10 various premium fillings and the taste would be different according to their types of fillings. Monsterwiches also provide a sandwich that consist of fresh vegetables, sliced cheese, beef, eggs and other healthy-induced ingredients that will surely make you satisfied with every bite. Apart of that, it is a sandwich that can be purchased regardless of the time. This is because it can be enjoyed anytime and anywhere such as banquets, parties or even having a meeting at office or can be as lunch box to the school and many more since it always relevant to bring anywhere that can be eaten with friends and family. In term of price selection is also not too expensive but affordable as it is worth it with the ingredients used which are quality and limited fillings. Finally, the taste is delicious and would be repeat once you have tried. However, by using the Facebook Page to make awareness about our product which promoted through posts that started with teaser and following with a soft sell and hard sell just to announce our precious product to be notice by audience in the pages. Even though it is quite challenging but it turning out with response from them which is able to provide good potential for the beginner business to grow faster and easier. Thus, the use of social media such as Facebook can have a good effect on sellers who need awareness about the products sold meanwhile it is also convenience to use by stages of ages.